2017
DOI: 10.2337/dc18-s007
|View full text |Cite
|
Sign up to set email alerts
|

7. Obesity Management for the Treatment of Type 2 Diabetes:Standards of Medical Care in Diabetes—2018

Abstract: The American Diabetes Association (ADA) “Standards of Medical Care in Diabetes” includes ADA’s current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, a multidisciplinary expert committee, are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed description of ADA standards, statements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(30 citation statements)
references
References 84 publications
0
28
1
1
Order By: Relevance
“…In our Japanese patients with type 2 diabetes, the combination of EI of ≥ 1967 kcal/day and PA of ≤ 9.9 metabolic equivalents (METs) h/week for men or that of EI of ≤ 1815 kcal/day and PA of ≤ 8.3 METs h/week for women was significantly associated with obesity. In contrast to current American Diabetes Association guidelines [ 9 ], which are primarily based on the results of intervention studies, the thresholds we found were much higher for EI and much lower for PA than the recommended values needed for obese individuals to lose weight. However, our thresholds were based on cross-sectional observations of Japanese participants whether or not they were obese.…”
Section: Discussioncontrasting
confidence: 99%
“…In our Japanese patients with type 2 diabetes, the combination of EI of ≥ 1967 kcal/day and PA of ≤ 9.9 metabolic equivalents (METs) h/week for men or that of EI of ≤ 1815 kcal/day and PA of ≤ 8.3 METs h/week for women was significantly associated with obesity. In contrast to current American Diabetes Association guidelines [ 9 ], which are primarily based on the results of intervention studies, the thresholds we found were much higher for EI and much lower for PA than the recommended values needed for obese individuals to lose weight. However, our thresholds were based on cross-sectional observations of Japanese participants whether or not they were obese.…”
Section: Discussioncontrasting
confidence: 99%
“…Healthcare professionals should consider prompt intervention in patients with high scores determined by this calculator, including setting a less stringent A1C target, adjusting antidiabetic treatment, obtaining frequent SMBG readings, applying lifestyle modifications with a regular meal schedule, and re-education. 2 , 39 …”
Section: Discussionmentioning
confidence: 99%
“… 1 International practice guidelines recommend that various classes of antidiabetic medications, along with lifestyle modifications, should be initiated to achieve glycemic goals. 2 , 3 In addition, a stepwise combination and intensification of medications are recommended for proper glycemic control in the updated guidelines. However, intensive glycemic control with antidiabetic medications or insulin injections can increase the risk of macrovascular events and mortality in patients with comorbidities and can be accompanied by the risk of hypoglycemia in patients with type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%
“…Current therapeutic strategies for attenuating obesity and insulin resistance include lifestyle modifications (e.g., diet, exercise, weight loss) prior to the administration of pharmacological agents (e.g., insulin-sensitizing drugs), which are prescribed only for patients with a body mass index (BMI) ≥27 kg/m 2 . Bariatric surgery is considered only for patients with a BMI of 30-40 kg/m 2 [9,10]. Due to the complications of insulin-sensitizer drugs, alternative remedies in the form of dietary agents to attenuate insulin resistance are receiving more interest.…”
Section: Introductionmentioning
confidence: 99%